Preliminary Observations on Air Layering in Pinus Roxburghii and P. Caribaea - Kedharnath, S.; Dhaundiyal, R. P. (Indian Forester, 1963)
Air layering was successfully done in Pinus roxburghii Sargent., and P. caribaea/I> Morelet. Very good root development was obtained in air layers tied on two-year old branches. One hundred per cent success was obtained in the air layers tried in April and May in the case of Pinus roxburghii and in June in the case of P. caribaea. Air layers on one-year-old branches failed to strike root in both the species.